Dissociated Therapeutic Regimen: Systemic Corticosteroids and Topical Natamycin in Traumatic Fungal Keratitis - Cyntia Dewi; Indira Putri (Sriwijaya Journal of Ophthalmology, 2025)
Introduction: Penetrating ocular trauma complicated by secondary fungal keratitis presents a fundamental inflammatory paradox in ophthalmology. While corticosteroids are clinically imperative to suppress trauma-induced fibrinoid syndrome and prevent phthisis bulbi, they are traditionally contraindicated in active mycotic infections due to the risk of potentiating fungal proliferation. This report evaluates a dissociated therapeutic protocol utilizing systemic corticosteroids alongside topical antifungals to navigate this therapeutic impasse. Case presentation: We present the case of a 26-year-old male sustaining a penetrating corneal injury from a metallic nail. Following primary repair, the patient developed a severe anterior chamber reaction with Standardization of Uveitis Nomenclature (SUN) Grade 3+ cells and a corneal infiltrate exhibiting feathery margins. Potassium Hydroxide 10% wet mount confirmed the presence of fungal hyphae. A dissociated therapeutic regimen was initiated: intensive topical Natamycin 5% administered hourly to target the ocular surface infection, synchronized with oral Methylprednisolone (24 mg/day; 0.4 mg/kg) to control intraocular inflammation via the systemic circulation. The regimen successfully decoupled the immune response. Intraocular inflammation resolved within 14 days, preventing the formation of permanent synechiae or cyclitic membranes. The fungal infection was eradicated, confirmed by negative serial corneal smears and the clinical resolution of the infiltrate into a stable leucoma. Visual acuity improved from Hand Motion (LogMAR 2.30) at presentation to 6/45 (LogMAR 0.88) at Day 35. No fungal recurrence was observed during the follow-up period. Conclusion: A dissociated strategy using intermediate-dose systemic corticosteroids to manage internal inflammation, while reserving the ocular surface for aggressive topical antifungal therapy, may offer a viable strategy for globe salvage in complex traumatic fungal keratitis cases where standard protocols are undefined.